Mission La Soledad, California. Founded 1791 (M. Kashower Company)
Back of postcard reads: 'La Soledad Mission was founded in 1791. Its ruins are located about thirty-five miles east of Monterey. Nothing has been done to preserve the church of 'Our Lady of Solitude.'